Effects of strong government measures against tobacco in Hong Kong. - Mackay, J M (1986)
The government of Hong Kong grasped the political nettle of control of tobacco in the early 1980s, since when a comprehensive policy of legislation, education, and publicity, together with large increases in taxation on tobacco products, has been introduced. This has led to almost all of the population of Hong Kong having knowledge of the harmful effects of tobacco and of antismoking measures taken by the government. From 1982 to 1984 the number of people who smoked daily fell appreciably from 888 300 to 744 500, a reduction of 16%, while the number of teenage smokers was halved (from 22 600 to 11 200). Government commitment is crucial in programmes against tobacco in developing countries; without it antismoking efforts are unlikely to be successful.